Forecasting Water Saturation of Fill Grounds in Urban Infrastructure Conditions by Mathematical Modeling Based on the Main Hydrophysical Characteristic - CHELOVECHKOVA, Anna V.; KOMISSAROVA, Irina V.; EREMIN, Dmitry I. (Journal of Environmental Management and Tourism, 2018)
A technique is proposed for forecasting water saturation of fill and undisturbed grounds used in construction when making a foundation. Dependencies are established between the content of individual granulometric fractions of grounds and their physico-mechanical properties. Reliable regression equations are obtained, which formed the basis of a mathematical model for predicting the water saturation of grounds. A software product has been developed, the work of which was tested using the example of the basic hydro-physical characteristics of the grounds differing in their properties (black earth and salt earth). The results obtained reliably prove the possibility of using the model and software product in a wide range of granulometric composition values and physical and mechanical properties of grounds.